Faculty Development for Online Teaching as a Catalyst for Change - McQuiggan, Carol A. (Online Learning, 2012)
This action research study explored the change in face-to-face teaching practices as a result of faculty professional development for online teaching. Faculty’s initial teaching model is typically born from that of their own teachers, and they teach as they were taught. However, few have any online experience as a student or a teacher. Learning to teach online may be a catalyst for faculty to reflect on and evaluate their current teaching practices. Data was collected through three rounds of action research that included individual interviews, participants’ reflective journalling activities, researcher’s journal and field notes, and classroom observations. The qualitative data analysis steps included data reduction, data display, and conclusion drawing/verification. The results of the study indicated that learning to teach online has the potential to transform faculty’s assumptions and beliefs about teaching, changing their face-to-face teaching practices. The identification of the aspects of professional development activities that were most effective in helping faculty to reflect on and question their previously held assumptions and beliefs about teaching will assist administrators and faculty development specialists move from one-size-fits-all programs to a redesign within an adult learning framework that supports opportunities for change.